Perancangan Sistem Informasi Manajemen Siswa SMP N 23 Semarang Berbasis Web Dan SMS (Studi Kasus SMP N 23 Semarang) (Information Technology and Telematics, 2013)
Information technology is evolving rapidly today, has prompted the acceleration in various fields. This also led to the emergence of advances in software and are offset by technological advancement and sophistication along with its hardware. Directly or indirectly, information technology has become an important part of many areas of life. SMS is one medium that is widely used by people today, because SMS has a very cheap rate. The need for faster information technology encourage accurate and actual. School information system via sms gateway school information display that can be accessed via phone, SMS to a predetermined format. This application uses the methodology of system development life cycle has five stages perancanaan, analysis, design, implementation and evaluation. The programming language used is PHP, using a MySQL database storage and SMS gateway using Gammu Engine. Thereby, overall system function to help smooth running education systems, by making use of information and communication technology as a media liaison between parents and the school, which will help keep the students in order to remain always guided toward positive activities and away from things that damage as well as directing them to become Human Resource potential for the development of the nation. Keywords: SMS (Short Message Service), system development life cycle, Engine SMS Gateway, System Information.